A tradição do pensamento da negatividade (da negatividade à Kehre heideggeriana) - Marçal Filho, José Carlos Gomes (2011)
The aim of this work is thematically analyze the concepts of nothing, ontological difference and Dasein transcendence - and its structural developments into the concepts of, and Being destination - as concepts that can converge to a specific current of Western thought that we will cal as negativity thought tradition. This approach frees these concepts from the strict heideggerian´s thought body and allows us to glimpse a tradition that, despite the traditional metaphysical ontology, points to a more radical ontological dimension. This tradition is understood as initiated by Philo of Alexandria, followed by Ammonius Saccas and Jamblico, developed by Plotinus and Proclus and christianized by the mysticism of Dinonisius, the Areopagite and Master Eckhart. From this last on, we can establish a link between this tradition and the Heidegger´s thought. We are not defining a mystical element into the Black Forest philosopher's thought, but providing clues that can harness the existential analytic approach and later developments of Heidegger's thought, the Kehre, with the the thinkers doctrines mentioned above. The links that will be established have convergences which can opening new possibilities up for thinking the collection of ancient ontology destruction, however, demonstrate that these similarities allow to contemplate the deeper dimension and these particular concepts and provide valuable clues for the interpretation not only within the Heidegger's thought, but also within the quoted tradition. It is a phenomenological-hermeneutic task capable of achieving a sense of historical and philosophical concepts, and finally set the parameters to define these points within the philosophy of Heidegger more clearly due to its link with a specific tradition.